Organic chemistry meets polymers, nanoscience, therapeutics and diagnostics - Rotello, Vincent M. (Beilstein Journal of Organic Chemistry, 2016)
The atom-by-atom control provided by synthetic organic chemistry presents a means of generating new functional nanomaterials with great precision. Bringing together these two very disparate skill sets is, however, quite uncommon. This autobiographical review provides some insight into how my program evolved, as well as giving some idea of where we are going.
Keywords: organic synthesis, supramolecular, nanoparticle sensing